Bioaccumulation and phytoremediation of some heavy metals (Mn, Cu, Zn and Pb) by bladderwort and duckweed - NAYYEF M. AZEEZ (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Azeez NM. 2021. Bioaccumulation and phytoremediation of some heavy metals (Mn, Cu, Zn and Pb) by bladderwort and duckweed. Biodiversitas 22: 3093-3098. This paper discussed the changes in some heavy metals (Mn, Cu, Zn, and Pb) in Utricularia vulgaris L. (Bladderwort) and Lemna minor L. (Duckweed) in the sewage treatment unit at the University of Basrah Campus, Iraq. For all examined heavy metals, the better accumulator was U. vulgaris than L. minor. This study proved that both plants significantly reduced the concentrations of heavy metals in wastewater. The efficiency of removing heavy metals was more than 68%. For both species, the bioconcentration factor (BCF) values of the tested metals were <1, and the BCFvalues decreased in the following order in both species: Pb>Mn>Cu>Zn. Reduction rates of pH, TSS, TDS, and conductivity were significant at the end of the experiment. The results showed that the tested macrophytes exhibit a good characteristic as bioaccumulators and could be effectively used in phytoremediation techniques.